Studi Stilistika Gaya Bahasa dalam Cerita Pendek Rashomon Karya Akutagawa Ryunosuke - Jashoshul Wathon (Universitas Dian Nuswantoro, 2021)
This paper discusses the style of language in Rashomon by Akutagawa Ryunosuke. The purpose of this study was to determine the language style in Rashomon. This is a qualitative project using a stylistic theory of language style. This research uses Rashomon's data source, Akutagawa Ryunosuke's short stories and analyzed by Keraf theory. The conclusion of this study is that the author uses a variety of language styles but is dominated by the comparative language style of humans and animals. a comparative language style is used to reinforce the author's ideas and have a dramatic effect on the reader.